Cardiovascular Rehabilitation in Patients with Diabetes Mellitus - Novita Lavi; Cholid Tjahjono; Laksmi Sasiarini (Universitas Brawijaya, 2022)
A hazard to global health is being posed by diabetes mellitus (DM). Macrovascular and microvascular abnormalities in blood vessels are one type of DM complication that might happen. In most cases, blood arteries, the brain, and the heart are affected by macrovascular problems. Obesity is well-known to have a substantial significant risk factor for coronary heart disease on its own (CHD). As a result, many persons with DM have a 2 to 4 times higher risk of dying from CHD than those without DM. In fact, different goal parameters (such glucose management, blood pressure, cholesterol status, or body composition) can improve with exercise training to varying degrees in each patient; here is where cardiovascular rehabilitation can help. To attain the best results, the type and intensity of exercise training must be tailored to the unique characteristics of each patient. The clinician's challenge is to teach the patient the skills necessary to maintain lifestyle modifications and to explain the relationship between exercise and blood sugar, BG goal ranges, and the types and amounts of activity that can be done safely.